Calcium Status with Some Inflammatory Markers in the Blood of Pregnant Women with Diabetic in Al-Samawa City/Iraq - Habiba Khdair (Journal of Global Pharma Technology, 2018)
Background: Diabetes mellitus (DM) is a group of metabolic diseases regarded as by hyperglycemia resulting from defects in insulin action, insulin secretion or both. The chronic hyperglycemia of DM is related with dysfunction of Kidneys and long-term damage, heart, blood vessels, and nerves. Menstruation in Women with Diabetes: Menstrual abnormalities, especially irregular rotations, are common in diabetic women, particularly in those with obesity and poor diabetic control. Many women with DM type 1 diabetes have ovulatory rotations, with secondary or oligo amenorrhea although oligo menorrhea is more common among diabetic women than general population Materials &Methods:  colorimetric analysis for Glucose concentration; had been applied for Erythrocyte Sedimentation Rate (ESR), Alkaline Phosphatase (ALP), Ca+2, and serum C-reactive protein (CRP) test *. Results & Conclusions : In this study There is a significant increase in (ESR, glucose, ALP,  Ca+2  level in pregnant patients as comparison the control group (P < 0.0383- 0.0002),  but  no significant in ( CRP level) in  pregnant patients as comparison the control group ,  there is  no significant difference between (ESR, Glucose, ALP,CRP , Ca+2) level in  pregnant patients with duration of the disease between patients ( duration  <12 weak) & (( duration  12-24) weak )  .There is a significant difference between ( Ca+2 ,CRP level ) level in  pregnant patients  with duration of the disease between patients ( duration  <12 weak) &( duration  > 24 weak). There is no significant difference between (ESR ,Glucose , ALP ) level in  pregnant patients  with duration of the disease between patients ( duration  <12 weak) &( duration  > 24 weak) There is a significant difference between (Ca+2,Glucose  ,CRP  ) level in  pregnant patients  with duration of the disease between patients ( duration  12-24 weak) &( duration  > 24 weak) . There is no significant difference between (ESR, ALP) level in pregnant patients with duration of the disease between patients (duration 12- 24 weak) & (duration > 24 weak).Key words: Glucose, Alkaline phosphatase (ALP), and Calcium (Ca) ;titer ELISA method for C-reactive protein (CRP) and vertical 20cm Western tube for erythrocyte sedimentation rate ( ESR).